Analisis Merkuri pada Rambut dan Kesehatan Efek Kesehatannya pada Mahasiswa FKM UMI yang Menggunakan Cosmetic Whitening Cream - Anugrah Maharani (Indonesian Journal of Science and Public Health, 2025)
Regulation of the Republic of Indonesia No. 445 of 1998 concerning Ingredients, Colorants, Substrates, Preservatives, and Sunscreens in Cosmetics prohibits the use of mercury in the addition of cream preparations, which includes a ban on the use of mercury cosmetic whitening creams for the face. The purpose of this study was to assess hair mercury and its impact on the health of FKM UMI students who use cosmetic whitening products. This type of research is quantitative, using cross-sectional study methodology, population 50, sample size calculated by the Slovin formula, sampling strategy based on purposeful sampling, and univariate and bivariate data analysis. Based on the results of the study, there was no significant correlation between the age of students when they first used cosmetic whitening cream and the mercury levels in their hair in 2018 (ρ value 0.911 < α (0.05)). However, there was a significant correlation between the frequency of using cosmetic bleaching cream and the mercury level in their hair in 2018 (ρ value 0.002 < α (0.05)). Based on the results of the study, students are advised to use cosmetic whitening creams according to their age and skin type. Considering the use of cosmetic whitening creams containing mercury can cause negative effects and health problems on the skin, it is hoped that the general public, especially FKM UMI students, can be more selective in choosing items to be used.